Modelagem de ações em jogos por meio da análise de RPGs - Franco, Artur de Oliveira da Rocha (2018)
Production of multimedia content, in particular, those involving interaction, has benefited from narratives to add value and depth to these works. Some games and other products have thus embedded dynamic stories which are affected by user interaction as a key feature. Such technology comprises an inherently interdisciplinary field of study called Interactive Storytelling (IS). Despite advances in the area, there is still a clear qualitative gap between narratives driven by humans and those generated by a computer using IS. This work is an initial investigative effort to tackle the problem of content analysis and generation in order to approach these types of narratives in the context of a popular form of IS: the Role-Playing Games (RPGs). Studies and analyzes of RPG games are carried out from a perspective that considers data extracted from RPG systems, electronic titles and games in internet forums to formulate hypotheses that may contribute to generating dynamic plots that can reflect the experience of tabletop RPG in the universe of digital games. The main contribution of this work is the analysis of adventures under a prism that considers both the structure of the narrative and the actions performed by the players within the scope of the popular D&D version 3.5 and of real adventures played by using internet forums as supporting technology.